Pemanfaatan Augmented Reality Sebagai Media Pembelajaran Protozoa - Fatki Sahida; Yusmedi Nurfaizal; Retno Waluyo (Politeknik Negeri Cilacap, 2020)
One of the efforts to improve the quality of education is the use of technology as a medium of learning. The learning media used by XYZ SMA teachers to teach about protozoa in class X MIPA still use graphic images in books. Problems that occur students find it difficult to understand the form, name and function of protozoa animals. To see protozoan animals in real terms, a microscop tool is needed, but there are not many microscopes owned by XYZ SMA. The purpose of this research is to make learning media with Augmented Reality technology about Protists on mobile devices. This application will only display four 3D objects, namely Paramecium, Flagellata, Sporozoa, and Amoeba. The method used by MDLC consists of six stages, namely concept, desing, material collecting, assembly, testing, and distribution. The results of this study are in the form of an Augmented Reality application as a learning medium for the discussion of protozoa. After testing using the alpha test, all buttons / menus run according to their function. Then in testing using the beta test, respondents stated that the application is very good for use as a learning medium.